2020
DOI: 10.3390/life11010022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quality of Life and Nutritional Status in Elderly Patients with Dysphagia in Order to Prevent Hospital Admissions in a COVID-19 Pandemic

Abstract: (1) Background: Oropharyngeal dysphagia (OD) is currently recognized as one of the geriatric syndromes due to its high frequency in older people and its associated complications, which have a direct impact on quality of life. The main objective is to determine the effectiveness of telehealth consultation for the re-evaluation of nutritional status and quality of life assessment in older people diagnosed with OD associated with active use of thickeners to prevent hospital admissions in a COVID-19 pandemic. (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
1
4
0
1
Order By: Relevance
“…Most of these individuals had complaints related to these domains, such as difficulty in dealing with the change in swallowing, presence of clearing, choking, and chewing difficulties, leftover food in the mouth, uncomfortable for not being able to eat everything, fear of choking, discouragement because they need to be careful when eating, and difficulty in social life due to changes in swallowing. These findings are in agreement with the studies of Fernández et al (2020), who demonstrated that the elderly present a greater change in the quality of the swallowing process because they are a population with a higher incidence of dysphagia (Fernández-Ruiz et al, 2020_. Tracheostomized individuals showed changes in the domains 1, 2, 3, 4, 6, 7, and 8. Most of these individuals had complaints related to these domains, such as difficulty in dealing with the change in swallowing, longer time needed for eating, presence of coughing, throat clearing, choking, and chewing difficulties, leftover food in the mouth, uncomfortable for not being able to eat everything, fear of choking, discouragement because they need to be careful when eating, and difficulty in social life due to changes in swallowing.…”
supporting
confidence: 92%
“…Most of these individuals had complaints related to these domains, such as difficulty in dealing with the change in swallowing, presence of clearing, choking, and chewing difficulties, leftover food in the mouth, uncomfortable for not being able to eat everything, fear of choking, discouragement because they need to be careful when eating, and difficulty in social life due to changes in swallowing. These findings are in agreement with the studies of Fernández et al (2020), who demonstrated that the elderly present a greater change in the quality of the swallowing process because they are a population with a higher incidence of dysphagia (Fernández-Ruiz et al, 2020_. Tracheostomized individuals showed changes in the domains 1, 2, 3, 4, 6, 7, and 8. Most of these individuals had complaints related to these domains, such as difficulty in dealing with the change in swallowing, longer time needed for eating, presence of coughing, throat clearing, choking, and chewing difficulties, leftover food in the mouth, uncomfortable for not being able to eat everything, fear of choking, discouragement because they need to be careful when eating, and difficulty in social life due to changes in swallowing.…”
supporting
confidence: 92%
“…Published and ongoing studies on the potential of technology to deliver physical, psychoeducational and psychosocial interventions remotely to people with dementia; 122 Alves et al., 2020 124 (Ballard; Manchester Camerata Ltd, NIHR) will offer insight into the acceptability of telehealth for those with more severe cognitive problems. Further research on the remote delivery of social care or befriending initiatives would also be important.…”
Section: Resultsmentioning
confidence: 99%
“…Muitos pacientes podem recuperar a função de deglutição normal ou funcional após intubação e traqueostomia com consequente decanulação em resposta efetiva à reabilitação fonoaudiológica 15 . As alterações de deglutição também influenciam inevitavelmente a qualidade de vida dos pacientes 16 , podendo apresentar correlação negativa e significante entre qualidade de vida e a gravidade da disfagia 17 nos pacientes internados com COVID-19.…”
Section: Introductionunclassified